Ambivalent Sexism and Alcohol Consumption in Adolescents from a Public High School in El Fuerte, Sinaloa, México - Arredondo-Palafox, Miguel Basilio; Ahumada Cortez, Jesica Guadalupe; Gámez-Medina, Mario Enrique; Valdez-Montero, Carolina; Mendoza-Armenta, Mayra (Horizonte Sanitario, 2025)
Objective: To examine the relationship between ambivalent sexism and alcohol consumption in adolescents. Materials and Method: A non-experimental quantitative study with a descriptivecorrelational and cross-sectional design was conducted among 139 high school adolescents. Sampling was random stratified. The questionnaires used were: the Inventory of Ambivalent Sexism for Adolescents (α=.85) and the AUDIT (α=.88). Results: It was found that the level of SA (rs= .212 p<.05) and SH (rs= .216 p<.05) are positively and significantly related to sensible consumption, a positive and significant correlation was also found between SB and the general score of the AUDIT (rs= .233 p<.05) consumption of sensible (rs= .208 p<.05), dependent (rs= .237 p<.05) and harmful (rs= .206 p<.05). Additionally, it was found that 30.9% consumed alcohol in the last month. On the other hand, the results of the AUDIT showed that 35.1% present a risk consumption. In the comparison of sexism by sex, men had higher scores of both sexism and consumption compared to women. Conclusion: It is necessary to carry out more research to know if the relationship between these variables is maintained in various population groups, in addition to allowing them to be addressed early for prevention. Keywords: Sexism; Alcohol Consumption; Adolescents.